Consumer ecological behaviour and attitudes towards pro-ecological activities in accommodation facilities by generation Z - Dębski, Maciej; Borkowska-Niszczota, Małgorzata (Turyzm/Tourism, 2020)
This is an empirical study that is based on the results of questionnaire research on ecological behaviour and consumer choices shown by generation Z and their attitudes towards pro-ecological practices implemented as part of ecological policies in accommodation businesses. At the same time, an attempt was made to find out whether the implemented ideas could encourage this generation to choose places offering practices friendly to the environment and thus be a source of competitive advantage of such locations. The description of the results was preceded by an overview of past research on the issue and theoretical background on sustainable consumption. An analysis of the results showed that Generation Z in most cases tried to limit their negative impact on the environment as well as trying to apply ecological guidelines in practice. Generation Z support pro-ecological behaviour on a daily basis, however, this is mainly true when it comes to behaviour bringing financial or health-related benefits. The young approve of most pro-ecological practices in the accommodation industry but they differ in preferences and in exchange for their support, they expect financial rewards. In conclusion, this generation rates more highly accommodation facilities implementing pro-ecological practices and this translates into a greater willingness to stay at such places.